Social Implications and Educational Strategies for Sustainability: HR Adaptation in Indonesiaʼs Rattan Industry - Wolor, Christian Wiradendi; et al. (European Journal of Social Science Education and Research, 2026)
The Indonesian rattan industry, as a labour-intensive and community-based export sector, is highly exposed to fluctuations in global trade policies, including protectionist tariffs imposed by the United States. This study examines the social implications of these trade disruptions on employment conditions and analyses how workers and industry actors develop adaptive and educational strategies to sustain livelihoods. Using a qualitative case study design, data were collected through in-depth interviews and participant observation in the rattan production centres of Trangsan and Rajapolah. The data were analysed thematically to identify patterns of social adaptation and workforce learning. The findings show that declining export demand has led to employment insecurity, reduced working hours, and increased vulnerability among informal workers. In response, industry actors adopted skills development initiatives, product diversification, community collaboration, and digital platforms. These practices indicate that human resource resilience is a socially embedded and educationally driven process shaped by informal learning, social support, and local innovation, contributing to workforce sustainability in traditional export industries.